2022
DOI: 10.1021/acs.est.2c02763
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Contaminants Stimulate Harmful Algal Organisms and Enrich Their Toxins

Abstract: A widespread increase in intense phytoplankton blooms has been noted in lakes worldwide since the 1980s, with the summertime peak intensity amplifying in most lakes. Such blooms cause annual economic losses of multibillion USD and present a major challenge, affecting 11 out of the 17 United Nations Sustainable Development Goals. Here, we evaluate recent scientific evidence for hormetic effects of emerging contaminants and regulated pollutants on Microcystis sp., the most notorious cyanobacteria forming harmful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 103 publications
1
18
0
Order By: Relevance
“…Toxic cyanobacteria are dominant organisms in harmful algal blooms. Harmful algal blooms have intensified worldwide since the 1980s due to anthropogenic (e.g., fertilizer use, population growth, and gross domestic product) and climatic (e.g., temperature, wind speed, atmospheric pressure, and rainfall) factors, and blooms are often more intense in less developed regions, such as in Asia, South America, and Africa . These factors suggest an enhanced risk for increased exposure to cyanotoxins, which differs among regions.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Toxic cyanobacteria are dominant organisms in harmful algal blooms. Harmful algal blooms have intensified worldwide since the 1980s due to anthropogenic (e.g., fertilizer use, population growth, and gross domestic product) and climatic (e.g., temperature, wind speed, atmospheric pressure, and rainfall) factors, and blooms are often more intense in less developed regions, such as in Asia, South America, and Africa . These factors suggest an enhanced risk for increased exposure to cyanotoxins, which differs among regions.…”
mentioning
confidence: 99%
“…These factors suggest an enhanced risk for increased exposure to cyanotoxins, which differs among regions. Anthropogenic contaminants in the environment can also stimulate the synthesis of cyanotoxins and their release in the environment, but recent studies indicated that the ingestion of anthropogenic chemicals by cyanobacteria can lead to the synthesis and release of novel cyanotoxins with the potential to lead to massive deaths of wild animals …”
mentioning
confidence: 99%
See 3 more Smart Citations